Exploring the Medieval Relationship between Islam and Christianity: Historical Context, Cultural Exchange, Religious Conflicts, and Significance - Barella, Yusawinur; Hasaruddin; Syukur, Syamzan (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research delves into the historical context, cultural exchange, religious conflicts, and significance of the relationship between Islam and Christianity during the Medieval. The study aims to gain an understanding of the complex dynamics, alliances, misunderstandings, and transformations that characterized this important era. By exploring primary sources, scholarly analysis, and historical records, this research uncovers the mutual influences, cultural exchanges, intellectual dialogues, and tensions arising from the coexistence and interaction of Islam and Christianity during the medieval period. The research contributes to a broader understanding of the historical legacies of Islam and Christianity, both separately and in relation to each other, highlighting the enduring consequences of their interaction on the development of religious traditions, intellectual thought, and cultural practices that continue to shape our world today. The author uses qualitative methods with literature study and documentation to collect historical information using historiography techniques. The results of the research show that this fluctuative relationship means that the relationship between the two religions cannot be fully generalized. There have been periods of cooperation and peace, but there have also been periods of tension and conflict between these two religions.